Experimentation with Realistic Mathematic Education Learning Approach to Problem Solving Skills on Social Arithmetic Material From Learning Style - M Ade Irawan; Subki Subki; Kiki Riska Ayu Kurniawati (IJECA (International Journal of Education and Curriculum Application), 2019)
The purpose of this research is to know the difference in problem-solving skills in social arithmetic material is reviewed from the learning style and which learning style has the best problem solving ability. The type of research used is the QUASI experiment. This study was conducted at MTS Putri NW Narmada 2018/2019 school year. The population in this study is all students of MTS Putri NW Narmada. Sampling techniques using Cluster Random Sampling, the sample used is Class VII F. Data collected with tests and tested with ANAVA one way. The results of the study stated that: Students with auditory, visual, and kinaesthetic learning styles have different mathematical problem solving skills. To further need a further test post Anava with Scheffe method. From the average comparison test results The average between the row and the column obtained the conclusion as follows: (1) in a double-comparison test between students with visual and auditory learning style of Ho received. Because Ho is accepted, students who have a visual and auditory learning style have the same problem solving skills. 2 In the double comparison test between students with auditory and kinaesthetic learning style is accepted by Ho. Since Ho is accepted, students with kinaesthetic and auditory learning styles have the same problem solving skills. 3 In the double comparison test between students with visual and kinaesthetic learning Styles Ho was rejected. Because Ho is rejected, there is a difference in problem solving skills between students with kinaesthetic learning style with students of visual learning style.